2015
DOI: 10.1017/s0007114515004626
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric characteristics and body composition in Mexican older adults: age and sex differences

Abstract: Anthropometric reference data for older adults, particularly for the oldest old, are still limited, especially in developing countries. The aim of the present study was to describe sex-and age-specific distributions of anthropometric measurements and body composition in Mexican older adults. The methods included in the present study were assessment of height, weight, BMI, calf circumference (CC), waist circumference (WC) and hip circumference (HC) as well as knee height in a sample of 8883 Mexican adults aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
6
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 22 publications
(41 reference statements)
5
26
6
2
Order By: Relevance
“…Body mass index use as a surrogate indicator of adiposity can be prone to errors because fat mass and fat free mass are not differentiated 34 , even though present results have been adjusted for the mid-arm muscle circumference. In men, the contribution of skeletal muscle mass to the total body weight is higher than in women, while in women, the proportion of fat mass/skeletal muscle mass is generally higher than in men 35 , 36 . Consequently, the association between overweight/obesity assessed through BMI and low gait speed can become more evident in women than in men.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Body mass index use as a surrogate indicator of adiposity can be prone to errors because fat mass and fat free mass are not differentiated 34 , even though present results have been adjusted for the mid-arm muscle circumference. In men, the contribution of skeletal muscle mass to the total body weight is higher than in women, while in women, the proportion of fat mass/skeletal muscle mass is generally higher than in men 35 , 36 . Consequently, the association between overweight/obesity assessed through BMI and low gait speed can become more evident in women than in men.…”
Section: Discussionmentioning
confidence: 89%
“…In line with our results, it was previously reported that elevations of several baseline adiposity measures were associated with a decline in gait speed, but also more strongly in women than in men 33 . Gender differences may be explained by the differences in body composition 34 , 35 . Body mass index use as a surrogate indicator of adiposity can be prone to errors because fat mass and fat free mass are not differentiated 34 , even though present results have been adjusted for the mid-arm muscle circumference.…”
Section: Discussionmentioning
confidence: 99%
“…The waist circumference (WC), which is an indicator of abdominal obesity, was measured to the nearest 0.1 cm, using a fiberglass tape measure and standard techniques, as described in the MHAS Manual of Procedures [ 53 ]. Based on the World Health Organization recommendations for WC cut-off points indicating overweight and obesity [ 57 ], and similar to an earlier study in older Mexican adults [ 58 ], we categorized the study participants as overweight/obese if their WC was >102 cm in men and >88 cm in women. Since BMI and WC are highly correlated (R 2 = 0.82, p < 0.001), and the majority of prior studies examined the association between BMI and circulating 25(OH)D concentration, we used BMI as the primary study exposure for making comparisons with earlier studies.…”
Section: Methodsmentioning
confidence: 99%
“…In older adults, males remain larger than females with increased height, body mass index and waist circumference while women have increased adiposity (138). This difference in body composition has failed to show much difference in actual drug distribution and any differences attributable to this can largely be explained by differences in total body mass (139).…”
Section: Sex Considerationsmentioning
confidence: 99%